2011
DOI: 10.15669/pnst.1.537
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Beam Data for Small Radiosurgical Fields: Comparison of CyberKnife Multi-sites in Korea

Abstract: The diode detector is recommended to measure the beam from CyberKnife recently. In this study, various detectors had been used to measure the beam data and compared that for each CyberKnife of domestic and foreign departments. All measurements of the beam data were performed by several detectors: diode detector, ion chamber, Gafchromic EBT film. These measured data compared with CyberKnife sites of the Korea. Also, these measured data are compared to a set of nationwide average data.For the collimators over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Although the edgeless technology allows for processing of both p-and n-type substrates, in this work, the devices adopted are only n-type, with the top side junction being p + −n and the lateral junction n + −n. The diodes have dimensions of 0.5 × 0.5 × 0.5 mm 3 [ Fig. 1(a)] and are packaged using the "dropin" proprietary CMRP technology [ Fig.…”
Section: A | Edgeless Detectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the edgeless technology allows for processing of both p-and n-type substrates, in this work, the devices adopted are only n-type, with the top side junction being p + −n and the lateral junction n + −n. The diodes have dimensions of 0.5 × 0.5 × 0.5 mm 3 [ Fig. 1(a)] and are packaged using the "dropin" proprietary CMRP technology [ Fig.…”
Section: A | Edgeless Detectorsmentioning
confidence: 99%
“…1,2 It requires an accurate target localization and identification which can be achieved by physical stereotactic immobilization devices registering patient to a fixed frame (e.g., Gammaknife) or by imaging-guided methods (such as Cyberknife Synchrony). 3 Due to the small beam size and precise conformation of dose distribution, SRS treatment can reduce radiotoxicity to normal tissues and organs at risk and improve the probability of local tumor control. 4 It is used often for intracranial (brain tumor) and recently extracranial lesions such as spine and breast tumors.…”
mentioning
confidence: 99%
“…The main advantage of using EBT3 films is that it has high spatial resolution than any solid-state detectors and is tissue equivalent. Use of diode detectors for relative measurements in small fields are promising due to their small sensitive volume and diode P detector is employed widely for commissioning of Cyberknife photon beams [23].…”
Section: Discussionmentioning
confidence: 99%
“…Jang et al . [11] used a diode detector, ion chamber, and Gafchromic EBT3 film to measure beam data and compared them with the data obtained from other clinics with CyberKnife systems. Their results revealed that the beam data acquired using different detectors showed good consistency within ±3% for collimators larger than 20 mm.…”
Section: Introductionmentioning
confidence: 99%